Exploring cypriot pharmacists' perceptions about their role in cardiovascular disease prevention: A descriptive qualitative study - Periklis Charalampous; Aliki Peletidi (Wolters Kluwer Medknow Publications, 2021)
Objective: The age-standardized prevalence of cardiovascular diseases (CVDs) among the Cypriot population in 2017 was estimated to be 5552 per 100,000. Therefore, the CVD prevention in Cyprus is of paramount importance. Pharmacists are one of the most accessible health-care professionals (HCPs) and the first port of call for the public. In Cyprus, there are 55.59 pharmacies per 100,000 inhabitants. Therefore, the role of Cypriot pharmacists (CPs) in primary CVD prevention is essential. This study aimed to explore both the existing and potential future roles of CPs in CVD prevention. Methods: A descriptive qualitative study employing structured interviews (SIs) was conducted. Initially, the CPs were identified through a list provided by the Cypriot Pharmaceutical Services. The researcher(s) then contacted CPs by telephone. Face-to-face interviews were scheduled based on the CP's availability. In total, 21 SIs were transcribed verbatim, coded, and analyzed thematically. SIs continued until data saturation was achieved. Findings: The findings are reported under the themes of pharmacists' knowledge and role, resources/tools available and training, communication and relations, and barriers. CPs expressed the need for training, and they are ready to have a more proactive role within the primary health care. The main barrier identified was the lack of responsiveness of the public and the lack of CP's time. Conclusion: CPs have the potential to actively participate in CVD prevention in Cyprus. CPs want to start offering primary CVD health services, with the smoking cessation being the first intervention.